2011
DOI: 10.1161/strokeaha.110.597930
|View full text |Cite
|
Sign up to set email alerts
|

Adults With Late Stage 3 Chronic Kidney Disease Are at High Risk for Prevalent Silent Brain Infarction

Abstract: Background and Purpose-The close relationship between stroke and chronic kidney disease (CKD) has been well-documented. However, few studies have focused on silent brain infarction (SBI) in CKD. We investigated the prevalence of SBI in different stages of CKD. Methods-We included 1312 participants aged 30 to 93 years who came from either a random sample of residents or from a group of physically examined subjects in the same community. Basic information, clinical evaluations, laboratory tests, and MRI images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 46 publications
(47 reference statements)
2
33
0
1
Order By: Relevance
“…In fact, of the studies examined in this review, four of five demonstrate a statistically significance relationship between prevalent SBI and levels of serum creatinine [45], estimated glomerular filtration rate [29] or cystatin C [58]. An association between SBI incidence and serum creatinine (OR: 1.5; 95% CI: 1.00, 2.40) [14] was also suggested.…”
Section: Non-cardiovascular Diseases Diabetes Mellitus and Chronic Kimentioning
confidence: 68%
See 1 more Smart Citation
“…In fact, of the studies examined in this review, four of five demonstrate a statistically significance relationship between prevalent SBI and levels of serum creatinine [45], estimated glomerular filtration rate [29] or cystatin C [58]. An association between SBI incidence and serum creatinine (OR: 1.5; 95% CI: 1.00, 2.40) [14] was also suggested.…”
Section: Non-cardiovascular Diseases Diabetes Mellitus and Chronic Kimentioning
confidence: 68%
“…Most remaining published CS studies give estimates in the 10% to 20% range (Table 1). In those undergoing RHS, the range has been greater still, from 5% [29] to 62% [21]. It is clear from these data that a statistically significant correlation exists between mean SBI prevalence and mean sample age, both when all 26 studies providing SBI prevalence data are compiled, and when community and clinic studies are assessed separately (Figures 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 87%
“…32 Several studies have demonstrated that a decreased eGFR is significantly associated with silent (asymptomatic or unreported) brain infarction, as detected by MRI ( Figure 1). [33][34][35] Cystatin C has a stronger association with silent brain infarction than do measures of creatinine or eGFR in individuals aged ≥65 years. 36 Importantly, and further supporting the bi-functional nature of disease interaction, silent brain infarction is an independent prognostic factor for kidney disease progression in patients with CKD.…”
Section: Microvascular Diseasementioning
confidence: 96%
“…There is evidence that points towards a positive association of chronic kidney disease with stroke [28,29] but some studies have also failed to confirm the association [30,31]. …”
Section: Discussionmentioning
confidence: 99%